Humanizing STEM Education in Primary Schools: Integrating Ethnopedagogy and Digital Learning for Sustainable Futures - Astrid Lekatompessy; Sarwi Sarwi; Woro Sumarni (Universitas Negeri Semarang, 2026)
The rapid advancement of science and technology, coupled with increasing global sustainability challenges, has highlighted the need for more holistic and culturally responsive STEM education. However, existing studies on ethnopedagogy, STEM education, digital learning, scientific literacy, and sustainability education are often investigated separately, resulting in fragmented pedagogical approaches. This study aims to synthesize current research trends and propose a conceptual Humanistic Ethno-STEM Model for Sustainable Citizenship that integrates local wisdom, cultural values, inquiry-based learning, STEM integration, digital storytelling, scientific literacy, and sustainability education. A Systematic Literature Review (SLR) following the PRISMA 2020 guidelines was conducted using publications retrieved from international databases. The selected studies were analyzed through descriptive analysis, bibliometric mapping, and thematic synthesis to identify dominant themes, research trends, and knowledge gaps. The findings revealed five major themes: Humanistic STEM Education, Ethnopedagogy, Digital Learning, Scientific Literacy, and Sustainability Education. The review indicates that although each theme contributes positively to student learning outcomes, relatively few studies integrate these dimensions within a unified educational framework. Based on the synthesis, a Humanistic Ethno-STEM Model for Sustainable Citizenship is proposed, consisting of four interconnected components: Input (local wisdom and cultural values), Process (inquiry-based learning, STEM integration, and digital storytelling), Output (scientific literacy, critical thinking, and cultural awareness), and Outcome (sustainable citizenship). The proposed model contributes a novel theoretical framework that bridges cultural responsiveness, technological innovation, scientific literacy, and sustainability-oriented learning. This study provides implications for curriculum development, instructional design, and educational policy while offering directions for future empirical validation, particularly in culturally diverse contexts such as Papua, Indonesia.